Immune Response to COVID-19 During Pregnancy - Chen, Ge; Liao, Qiuyue; Ai, Jihui; Yang, Bin; Bai, Hualin; Chen, Jing; Liu, Fengyuan; Cao, Yang; Liu, Haiyi; Li, Kezhen (Frontiers in Immunology, 2021)
Pregnant women are generally more susceptible to viral infection. Although the impact of SARS-CoV-2 in pregnancy remains to be determined, evidence indicates the risk factors for severe COVID-19 are similar in pregnancy to the general population. Here we analyzed clinical symptoms and outcomes of 20 pregnant and 299 reproductive-aged non-pregnant female COVID-19 patients who were hospitalized during the same period. Laboratory measurements were compared among mild cases. Our study found that pregnant patients showed enhanced innate immune response evident by higher neutrophils, C-reactive protein and IL-6. We applied lymphocyte subsets analysis in 7 pregnant patients and 19 non-pregnant patients, and cytokines, chemokines and growth factors (CCGFs) profile from 11 pregnant and 4 non-pregnant female patients. We identified potential enhanced NK cell activity and suppressed cytokine cascade in pregnant patients, which may be essential in contributing to anti-SARS-CoV-2 immunity in pregnancy.